Rural resources as tourism capital: the case of Setiu Wetlands, Terengganu, Malaysia - Siow, May Ling; Ramachandran, Sridar; Shuib, Ahmad; Nair, Madhavan Balan; Mohammad Afandi, Syamsul Herman; Prabhakaran, Sudesh (Forestry Department Peninsular Malaysia, 2013)
Rural resources are subjected to pressure from impacts of economy, social, politics and environment. This paper examines the relationship of rural tourism resources and the advantages of adopting sustainable developments policies and strategies based on a case study in Setiu, Terengganu. A four-step strategy was employed in achieving the goals of this case study. The first step was identifying the rural capital available in Setiu. The second step was to determine the role of rural tourism capital in Setiu. The third step was to identify the possible investment potentials and challenges in rural capital and the final step was to examine the contribution of rural resources towards scaling-up the tourism industry in Setiu. This paper also highlights the profile of rural tourism by revisiting resources as an 'asset' of the tourism industry. This case study discusses some of the advantages of re-moulding the rural resource as 'tourism capital'. An assumption, which can be derived, is that the rural resource as tourism capital offers a comprehensive and integrated understanding of the rural tourism production system. This will be beneficial if rural communities utilise the potential benefits and effectively handle rural resources. This framework will lead to higher growth utilising tourism capital and thus increasing the standard of living of rural community in Setiu.